KESADARAN WAJIB PAJAK, PENERAPAN E-BILLING, PENERIMAAN PAJAK DIMODERASI PEMAHAMAN TEKNOLOGI INFORMASI - Suyanto; Fajrin, Syifa Dwina (AKUNTANSI DEWANTARA, 2024)
The purpose of this study is to examine the impact of taxpayer awareness and the application of e-billing on tax revenue which is then strengthened by the understanding of information technology. This study involved 114 registered taxpayers at the Sleman and Yogyakarta Tax Office. The research method applied is Partial Least Square (PLS) modeling using smartPLS 4.0 software assistance to analyze the data. This study shows that partially taxpayer awareness and the application of e-billing have an influence on tax revenue, and understanding information technology is able to strengthen the relationship between taxpayer awareness and the application of e-billing on tax revenue partially. this study adds the moderating variable of understanding information technology which is still rarely studied as a novelty in research.